2002
DOI: 10.1080/02652030210151877
|View full text |Cite
|
Sign up to set email alerts
|

Migration of surrogate contaminants in paper and paperboard into water through polyethylene coating layer

Abstract: The migration of five surrogate contaminants, anthracene, benzophenone, dimethyl phthalate, methyl stearate and pentachlorophenol, from paper and paperboard into water through a polyethylene (PE) coating layer was investigated. Virgin paper and paperboard coated with PE films of 0.012 and 0.030 mm thickness were spiked evenly with standard 1-ml solutions containing 5mg of each surrogate. The spiked papers were placed in contact with the PE coating layer at 10 and 24 degrees C for 21 days. The resulting surroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…This indicates that the types of substances known to occur in packaging materials can transfer through the gas phase. Other researchers have shown that some primary packaging materials are not barriers to transfer (Choi et al 2002;Anderson and Castle 2003;Song et al 2003). Anderson and Castle, in studies on migration of benzophenone from cartonboard to foodstuffs, noted that there can be transfer to foods even where the foodstuff is packaged in an intervening plastic wrap.…”
Section: Introductionmentioning
confidence: 94%
“…This indicates that the types of substances known to occur in packaging materials can transfer through the gas phase. Other researchers have shown that some primary packaging materials are not barriers to transfer (Choi et al 2002;Anderson and Castle 2003;Song et al 2003). Anderson and Castle, in studies on migration of benzophenone from cartonboard to foodstuffs, noted that there can be transfer to foods even where the foodstuff is packaged in an intervening plastic wrap.…”
Section: Introductionmentioning
confidence: 94%
“…Plastic layers may potentially represent an FB; they are low cost, readily available and widely used for controlling permeation of water vapour and oxygen. Laminated or coated with plastic materials, P&B have long been used for contact with liquid or solid with high moisture or free-fat contents; actually, polyolefins such as polyethylene (PE) and polypropylene (PP) show only poor performance (Choi et al 2002), only polyethylene terephthalate (PET) is considered the most promising polymer as an FB material (Franz 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have studied how photoinitiators can reach the foodstuffs and have identified two main routes: 11,12 (a) direct transfer by permeation from the outer printed surface through different layer(s) of packaging, or by offset (transfer of the photoinitiators during storage of the printed material in reels or stacks), 13,14 and (b) indirect transfer by gas phase, for volatile photoinitiators such as benzophenone and derivatives, see Figure 14.1. 15,16 However, it is not only the starting substances that can migrate to the foodstuffs and contaminate them.…”
Section: Introductionmentioning
confidence: 99%